2017
DOI: 10.1002/sctm.16-0470
|View full text |Cite
|
Sign up to set email alerts
|

Immature Midbrain Dopaminergic Neurons Derived from Floor-Plate Method Improve Cell Transplantation Therapy Efficacy for Parkinson's Disease

Abstract: Recent reports have indicated human embryonic stem cells‐derived midbrain dopamine (mDA) neurons as proper cell resources for use in Parkinson's disease (PD) therapy. Nevertheless, no detailed and systematic study has been conducted to identify which differentiation stages of mDA cells are most suitable for transplantation in PD therapy. Here, we transplanted three types of mDA cells, DA progenitors (differentiated in vitro for 16 days [D16]), immature DA neurons (D25), and DA neurons (D35), into PD mice and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 36 publications
(64 reference statements)
0
34
0
1
Order By: Relevance
“…However, we lacked a systematic evaluation of whether dopaminergic progenitors or more mature neurons generated via this protocol produced the best long‐term survival and functional restoration. In their recent STEM CELLS Translational Medicine article, researchers led by Eng King Tan (National Neuroscience Institute), Steve Oh (A‐Star), and Li Zeng (National Neuroscience Institute, Singapore) employed the floor‐plate method to generate cells representative of different stages of dopaminergic differentiation and assessed engraftment, survival, differentiation, maturation, and functional recovery in a mouse model of Parkinson's disease. Qiu et al discovered that dopaminergic progenitors, immature neurons, and mature neurons all engrafted into host brains with high viability rates with no sign of neural overgrowth, necrosis, or apoptosis.…”
Section: Related Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we lacked a systematic evaluation of whether dopaminergic progenitors or more mature neurons generated via this protocol produced the best long‐term survival and functional restoration. In their recent STEM CELLS Translational Medicine article, researchers led by Eng King Tan (National Neuroscience Institute), Steve Oh (A‐Star), and Li Zeng (National Neuroscience Institute, Singapore) employed the floor‐plate method to generate cells representative of different stages of dopaminergic differentiation and assessed engraftment, survival, differentiation, maturation, and functional recovery in a mouse model of Parkinson's disease. Qiu et al discovered that dopaminergic progenitors, immature neurons, and mature neurons all engrafted into host brains with high viability rates with no sign of neural overgrowth, necrosis, or apoptosis.…”
Section: Related Articlesmentioning
confidence: 99%
“…In the second of our Featured Articles this month published in STEM CELLS , Kwak et al describe a novel method for the generation of homogenous hPSC‐derived midbrain‐like organoids that may prove useful for the in vitro modeling of Parkinson's disease . In a Related Article published in STEM CELLS Translational Medicine , Qiu et al reported that transplantation of immature midbrain dopaminergic neurons derived from hPSCs prompted enhanced functional recovery in a Parkinson's disease mouse model when compared with mature neurons and progenitor cells …”
mentioning
confidence: 99%
“…Si la réplication in vitro des voies de signalisation qui déterminent le destin cellulaire au cours de l'embryogénèse permet de produire des cellules différenciées spécifiques d'un lignage, se pose néanmoins la question du stade optimal de différenciation auquel ces cellules doivent être transplantées. Dans un modèle murin de maladie de Parkinson, des neurones dopaminergiques immatures post-mitotiques ont ainsi été identifiés comme étant les plus efficaces, comparés à des cellules à des stades plus précoces ou plus tardifs de différenciation [36]. Dans le diabète, les données vention du rejet est très dépendante du mécanisme d'action présumé des cellules greffées.…”
Section: La Maturation Des Cellules Cardiaques Dérivées Des Cspunclassified
“…The generation of midbrain DA neurons from hPSCs represents a potentially exciting treatment for the neurodegenerative disorder PD. Researchers from the laboratories of Eng King Tan, Li Zeng (National Neuroscience Institute), and Steve Oh (A*STAR, Singapore) sought to discover the optimal maturity of DA cells in their recent S tem C ells T ranslational M edicine article given the lack of detailed and systematic studies. Following differentiation of human embryonic stem cells via a floor plate‐based differentiation method, the authors discovered that immature DA neurons (25 days) and DA neurons (35 days differentiation), but not DA progenitors (16 days), permitted higher levels of functional recovery following transplantation into a PD mouse model.…”
Section: Related Publicationsmentioning
confidence: 99%